Tradition to Pathogenesis: A Novel Hypothesis for Elucidating the Pathogenesis of Diseases Based on the Traditional Use of Medicinal Plants - Kuchta, Kenny; Cameron, Silke (Frontiers in Pharmacology, 2021)
Traditional medicines embody knowledge on medicinal plants that has been accumulated through cultural evolution over millennia. In the latter half of the 20th century, two approaches to medicinal plant research have been established: the "Bench to Bedside" and the "Bedside to Bench" approaches which serve primarily for the development of more efficient therapeutics. Here, we propose a third, novel approach: from "Tradition to Pathogenesis" which aims to understand the pathogenesis of diseases based on the cultural evolution of their respective empirical treatments. We analyse multiple examples of diseases where the acting mechanism of traditional treatments across multiple cultures points to the pathogenesis of the respective disease. E.g. many cultures traditionally treat rheumatism with anti-bacterial herbs, which is at odds with our current understanding that rheumatism is an aseptic inflammation. Furthermore, gastric ailments have traditionally been treated with anti-infectious herbs indicating local infections, as demonstrated by the discovery of Helicobacter pylori as a common cause of gastric ulcer. Understanding traditional treatments can thus help to elucidate the pathogenesis of a disease.